PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN SAPI PERAH DI DESA GEGER KECAMATAN SENDANG KABUPATEN TULUNGAGUNG - Lailatul Izza; Maftuhul Ihsan (Institut Agama Islam Tribakti Kediri, 2023)
Community empowerment through the management of dairy cows is one of the flagship programs of the Tulungagung Regency Government which aims to improve the economy of the people of Kampung Susu Geger, who incidentally are dairy farmers so that farmers can spread their wings in marketing the livestock products they have managed through this empowerment after that. Asset-Based Community Development (ABCD) is one approach in The process of community empowerment through the management of dairy farms in Geger Village. Data collection techniques used were: (1) observation, (2) interviews, and (3) documentation. This paper has results showing that: (1) The process of Community Empowerment through the management of dairy farms in Geger Village is generally quite mature in terms of planning by selecting activities based on priority needs of community groups. In general, its implementation can support the success of the Empowerment Program through managing dairy farms and improving the community's economy.